The Integrated CIPP Evaluation Model of Maqāṣid al-Syarī‘ah: An Alternative for Measuring Substantive Quality in Islamic Education Policy Management - Fatimatuz Zahro; Samsu (Al-Qalam Institue, 2026)
This study aims to reconstruct an integrative policy evaluation framework for Islamic education management by combining Daniel Stufflebeam’s Context, Input, Process, Product (CIPP) model with the principles of Maqāṣid al-Sharī‘ah. The study employs a qualitative library research method through the collection, review, and critical analysis of primary and secondary literature related to public policy evaluation and the philosophy of Islamic education. The findings reveal that conventional evaluation models predominantly emphasize administrative compliance, efficiency, and measurable outputs, while paying limited attention to spiritual, ethical, and societal dimensions that constitute the core objectives of Islamic education. To address this gap, the study develops a modified CIPP framework that evaluates context, input, process, and product dimensions through the lens of the five essential objectives of Maqāṣid al-Sharī‘ah: protection of religion, intellect, life, lineage, and wealth. The integration of these dimensions transforms educational evaluation from a rigid administrative mechanism into a strategic instrument for promoting institutional quality, public benefit, and sustainable development. The study implies that policymakers, administrators, and evaluators can utilize this framework to conduct more comprehensive, value-oriented, and contextually relevant evaluations of Islamic educational institutions.